Analisis Berorientasi Objek Dalam Penentuan Tingkat Kreativitas Siswa Dengan Metode Fuzzy Mamdani - Indra Kurniawan; Rahman Abdillah (SAP (Susunan Artikel Pendidikan), 2018)
Problem-solving skill requires the ability to think creatively in exploring various alternatives or solutions. Someone’s ability to think has different levels depending on works he produces. Therefore, it is necessary to carry out an analysis of the determination of student’s creativity level by employing a fuzzy mamdani method. The aim of this research is to know the process of determining the student’s creativity level by using a fuzzy mamdani method. The research applies a survey method with a qualitative research model in which the data are collected by observation, interview and literature review techniques